Northern Lighthouse: Lúcia Chedieck's talent and her pioneering female role in lighting, from Belém-PA to the world (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
Lúcia Chedieck was born in Belém - Pará, set designer and light designer who opened paths for other women to invest in technical careers in this region. In an interview with A LUZ EM CENA, she exposes some experiences and reports her struggles in the face of adversities in the labor market for women in the technical and cultural sector, which are still common today, she also discusses the need for dialogues for professional training and the need for experiences to carry out work in scenic lighting. From the first generation of northern lighting designers, she shares with us her experiences and productions with scenography and lighting in architecture, performing arts and plastic arts.
Keywords: scenic lighting; northern illuminator; light dialogues